A three-dimensional Josephson parametric amplifier. (1st June 2022) - Mahboob, Imran; Toida, Hiraku; Kakuyanagi, Kousuke; Nakamura, Yasunobu; Saito, Shiro
Abstract: A Josephson parametric amplifier (JPA) is executed in a three-dimensional (3D) microwave cavity by coupling it to a superconducting quantum interference device (SQUID) that is embedded in a two-dimensional resonator. The JPA is activated in a three-wave mixing configuration by injecting ac magnetic flux, at twice the 3D cavity frequency, into the SQUID. An 8.3 GHz cavity is measured in a non-degenerate phase-insensitive configuration which yields gains in excess of 40 dB, where a 20 dB gain results in an operational bandwidth of 0.4 MHz, a 1 dB compression point of −115 dBm with half a quantum of added noise.